Service Quality Analysis of PT. Pos Indonesia (Persero) Sibolga City Branch 22500 - Tanjung, Selvira Wardani; Nurbaiti, Nurbaiti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The public service system engaged in self-service, for example, is PT. Pos Indonesia (Persero). However, the service system provided by PT. The Persero in the field conditions are still found to be lacking, so that many consumers complain about the services provided. This condition is caused by the many competitors engaged in shipping services that offer guaranteed package delivery, wider coverage, accuracy and speed to arrive at the destination city and others. The purpose of this study was to determine the quality of service in the delivery of Persero packages at the Sibolga City branch of 22500. The results of this study are that there is an increase in the delivery target each year starting from 2018-2021. The conclusion is the service system provided by PT. Pos Indonesia, the Sibolga City branch, has provided quite good service to consumers. Then in terms of the facilities and infrastructure in the place, it is also good. These facilities and infrastructure are included in the physical evidence indicators. Furthermore, in terms of responsiveness indicators explained that employees always provide various kinds of information at PT. Pos Indonesia Sibolga City branch to consumers. So that the average consumer who came to the place gave a positive response to the services of PT. Pos Indonesia, Sibolga City branch